Legal Protection for Auction Winners Whose Items Are Still Held by The Debtor According to Law Number 4 of 2004 on Auctions - Rusmana, R. Anggi Gilang; Irawan, Hagi Muhamad Fauzan; Maskanah, Ummi (Golden Ratio of Data in Summary, 2025)
This research discusses the legal protection for auction winners whose items are still held by the debtor, analyzed based on Law Number 4 of 2004 on Auctions. An auction is one way to enforce creditors' rights against debtors who cannot fulfill their obligations. In this study, the author examines the provisions in Law Number 4 of 2004, and the applicable legal practices to provide an overview of the legal steps auction winners can take to obtain the items they have won. The research findings indicate that although the auction winner has the right to the items once the auction process is complete, there is a legal protection mechanism that must be followed to obtain those items, including through the execution of goods by the auction official. This study also highlights the importance of legal protection for auction winners so that the applicable procedures can effectively protect their ownership rights over the auctioned items.